Sincrofasores em sistemas de potência: aplicações na estimação de estado - Moraes, Rui Menezes de (2009)
This Thesis evaluates the use of synchronized phasor measurements, applying Phasor Measurement Units (PMUs) in wide area electrical power systems, as the Brazilian Interconnected System (SIN). The deployment in large scale of PMUs presents some unique challenges, as: (i) the great number of measuring involved; (II) the huge volume of data to be managed; (III) the data communication reliability over long distances; (IV) the use of multivendor PMUs (different models or manufacturers); (v) and the need to comply with different applications requirements. This research analyzed the functional and architectural requirements for a wide area phasor measurement system and presents proposals that make possible its successful application, evaluating the current state-of-the-art of the synchronized measurement technology and establishing a strategy for the deployment of these systems with success in wide area electrical power systems. The research still focuses the application of synchronized measurement technology in a basic tool for the operation of modern electrical power systems - the State Estimators found in Energy Management Systems. Simulation studies were conducted to evaluate different ways of including PMU measurements in the state estimation process, regarding: accuracy of different measurement system components; the measurement process itself; state estimation algorithms and data validation.